2019
DOI: 10.33258/birci.v2i1.178
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence the Reality of Performance Accountability in Government Institutions (Empirical Study in Government Deli Serdang District)

Abstract: This study aims to determine whether the commitment of management, decision making authority, organization culture is partially affected and simultaneously to the accountability performance in government agency to improve government performance. This research method is to use a casual research design. The sample is determined by using the technique of purposive sampling.The population in this research are all employees of the Unit of work Tools (SKPD) Government of Deli Serdang. The sample used in this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The results of this research are in line with previous research conducted by Fadhlurrohman, Budiman, and Khairina (2021), Sadad, Pituringsih and Irwan (2016), and Syahputri et al, (2019) which stated that organizational culture affects the performance of local government organizations. However, the results of this research contradict Indudewiet al, (2021) based on his research in Regional Apparatus Organizations (RAO) at the Yogyakarta Special Region Government (DIY) which concluded that organizational culture in a high context had no effect on government performance.…”
Section: Organizational Culture On the Performance Of Government Agen...supporting
confidence: 91%
See 1 more Smart Citation
“…The results of this research are in line with previous research conducted by Fadhlurrohman, Budiman, and Khairina (2021), Sadad, Pituringsih and Irwan (2016), and Syahputri et al, (2019) which stated that organizational culture affects the performance of local government organizations. However, the results of this research contradict Indudewiet al, (2021) based on his research in Regional Apparatus Organizations (RAO) at the Yogyakarta Special Region Government (DIY) which concluded that organizational culture in a high context had no effect on government performance.…”
Section: Organizational Culture On the Performance Of Government Agen...supporting
confidence: 91%
“…According to De Long and Fahey (2017), it is stated that organizational culture is needed to increase knowledge sharing and creative thinking to support organizational success. This statement is in line with the results of research conducted by Fadhlurrohman, Budiman, and Khairina (2021), Sadad, Pituringsih, andIrwan (2016), andSyahputri et al, (2019), namely organizational culture affects the performance of local government organizations. However, this is different from the statement of Indudewi et al, (2021) in the results of their research which states that organizational culture in a high context has no effect on government performance.…”
Section: Introductionsupporting
confidence: 89%
“…Preventing false financial reporting is reflected in the control environment; identification of opportunities and opportunity assessment can improve quality financial reporting. This finding suggests that preventing false financial reporting has an influence on the quality of financial reporting (Hussain, Rigoni, & Orij, 2018;Khalique, Isa, Nassir Shaari, & Ageel, 2011;Syahputri, Dalimunthe, Sabrina, & Rahmadhani, 2019).…”
Section: Hypothesis Testing Resultsmentioning
confidence: 97%